Pengaruh Pengetahuan dan Sikap terhadap Praktik Investasi Mahasiswa di Pasar Modal Syariah: Pendekatan Teori KAP - Jeihan Ali Azhar; Fajar Sodik; Alifia Nur Zaida; Khusnul Zulmiati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study aims to analyze the influence of students' knowledge and attitudes towards investment practices in the Islamic capital market. The model in this study adopts concepts from KAP theory (Knowledge, Attitude, and Practice). This research is a type of research using a quantitative approach. Data collection was carried out by distributing questionnaires to respondents using purposive sampling technique. Respondents in this study were students studying in the province of D.I. Yogyakarta. The data analysis technique was carried out using the SEM-PLS technique through the Warp PLS 6.0 analysis tool. The results of the SEM analysis show that knowledge and attitudes have a significant influence on student practice in relation to investment in the Islamic capital market. The implications of this research are expected to be input for practitioners who are active in the Islamic capital market industrial sector to be able to provide more attractive investment products. Thus, this research can be a means to encourage people, including the millennial generation, to start investing as early as possible as a form of financial planning in the future